The implications of pharmacogenomics in the treatment of HIV-1-infected patients of African descent - Hector Clarke; Shaker A Mousa (Dove Medical Press, 2009)
Hector Clarke, Shaker A MousaThe Pharmaceutical Research Institute, Albany College of Pharmacy and Health Sciences, Rensselaer, NY, USAAbstract: One of the great advances in the treatment of HIV-1 infection was the development of the highly active antiretroviral therapy (HAART). Although this treatment strategy is highly effective in many individuals, interpatient variability of drug response and high incidences of short- and long-term toxicities remain significant problems associated with this treatment. Logically, pharmacogenetic differences among HIV-1-infected individuals are thought to represent important factors contributing to antiretroviral drug response. Studies have identified polymorphisms in drug-metabolizing enzymes, drug transporters, and most recently the human leukocyte antigen locus that appears to have significant effects on the clinical outcomes of antiretroviral therapy. Furthermore, some studies have shown that many of these crucial polymorphisms are more likely or less likely in certain populations. This review investigates the potential role of pharmacogenomics in the management of HIV-1 infection in people of African descent.Keywords: HIV, AIDS, pharmacotherapy, pharmcogenomic, genetics, African populations, personalized medicine